High preharvest donor Foxp3 mRNA level predicts late relapse of acute lymphoblastic leukaemia after haematopoietic stem cell transplantation. (15th February 2021) - Jacobsen, Niels; Frisch, Tina; Keiding, Niels; Heilmann, Carsten; Sengeløv, Henrik; Madsen, Hans O.; Marquart, Hanne; Dickmeiss, Ebbe; Andersen, Mette K.; Christiansen, Claus B.; Ryder, Lars P.
Abstract: Objectives: The curative effect of allogeneic haematopoietic stem cell transplantation (HSCT) for acute leukaemia is due in part to the donor T cell–mediated graft‐versus‐leukaemia immune reaction (GvL). Several studies have suggested that donor CD25+CD4+Foxp3+regulator T cells (Tregs) may decrease graft‐versus‐host disease (GvHD) without abrogating GVL. This notion may need modification in acute lymphoblastic leukaemia (ALL). Methods: Foxp3 mRNA level was measured by qPCR in preharvest donor blood CD4+ T cells. The study comprised 45 patients with ALL in 1st or 2nd CR who received myeloablative HSCT using T‐replete bone marrow grafts. Results: Relapse occurred in 17 patients median 363 days after HSCT. The relapse risk was estimated by Cox univariate and multivariate proportional hazard regression. The proportionality assumption was met by analysing the preharvest donor Foxp3 mRNA level as a time‐dependent covariate. Early relapse was not modified by the Foxp3 mRNA level. However, a higher Foxp3 mRNA level was associated with a significantly increased relapse risk after day 363 after transplantation, compatible with inhibition of GvL. In contrast, a higher preharvest donor CD4+ T‐cell concentration was associated with reduced relapse risk. Conclusion: A higher preharvest donor Foxp3 mRNA level may be predictive of late ALL relapse after HSCT.